A critical review for machining positioning based on computer vision. (November 2021) - He, Wenbin; Jiang, Zhiwen; Ming, Wuyi; Zhang, Guojun; Yuan, Jie; Yin, Ling
Abstract: With the rapid development of science and technology, the manufacturing industry has to cope with increasingly stricter requirements in terms of the quality of processed products. To improve production flexibility and automation, computer vision is widely used in machining due to its safety, reliability, continuity, high accuracy, and real-time performance. In this study, a comprehensive review of positioning methods for workpieces in machining is presented from the perspective of computer vision technology. First, the key technologies in image acquisition are described in detail, and a analysis of different lighting modes is conducted. Second, image preprocessing is described by summarizing enhancement and image segmentation methods. Third, from the perspectives of accuracy and speed, feature extraction methods are compared and evaluated. Next, the existing applications of visual positioning technology in machining are discussed. Finally, the existing problems are summarized, and future research directions technology suggested. Highlights: A review of visual positioning methods for workpieces in machining is presented. Analyze the essentials of optical system, and propose the issues focused. Research and summarize the effects of image preprocessing on positioning result. The methods of feature extraction for processing positioning are summarized. The improvement methods of visual positioning technology are put forward.